Candida and Toll-Like Receptors - Demirezen, Şayeste; Yücel, Ayşegül; Beksaç, Mehmet Sinan (Gynecology Obstetrics & Reproductive Medicine, 2012)
Candida is a dimorphic fungus living as a commensal organism in human vagina. However it can cause infection under some conditions. Some factors, such as stratification of vaginal epithelial cells, natural flora and acidic pH, prevent infection by this organism. Recent studies identified that Toll-like receptor (TLR) proteins also play a role in protecting against infection. These receptors recognize Candida cell wall components such as β-glucans, mannoproteins and chitin. When TLR’s interact with these biomolecules, TLR signaling pathway become active and various cytokines are produced. Morphogenesis from yeast form to pathogenic hyphal form is inhibited by these cytokines. In our review, we aim to clarify Candida, vulvovaginal candidiasis, TLRs and relationship between TLRs and Candida.